Oncolytic viral therapy for nonmelanoma skin cancer and cutaneous lymphoma – A systematic reviewCapsule Summary - Felicia Li Ling Ong, MBBS, MRCP; Darryl Kai Xian Chin; Yiming Zhu; Choon Chiat Oh, MBBS, MRCP, MSc (JAAD International)
The rising incidence and consequent health care burden of nonmelanoma skin cancers, including cutaneous lymphomas, are a growing cause for concern. Oncolytic viruses (OVs) are emerging immunotherapies with limited literature on their use. We conducted a systematic review to evaluate their role in nonmelanoma skin cancer and cutaneous lymphoma treatment (CRD42024526854). We identified 11 published studies involving a total of 20 patients (squamous cell carcinoma n = 3, Merkel cell carcinoma n = 7, cutaneous T cell lymphoma n = 9, basal cell carcinoma n = 1). OVs used include Talimogene laherparepvec (73%, n = 8), measles virus (9%, n = 1), vesicular stomatitis virus (9%, n = 1), and adenovirus (9%, n = 1). Complete response occurred in 67% (n = 2) of squamous cell carcinoma cases, 85% (n = 6) of Merkel cell carcinoma cases, and 11% (n = 1) of cutaneous T cell lymphoma cases. The most common adverse event was fever or flu-like symptoms (n = 5, 25%). Fourteen unpublished clinical trials investigating regimes such as OV monotherapy (43%, n = 6), combination therapy with existing immunotherapy (21%, n = 3), and comparing OV combination versus monotherapy (29%, n = 4) or versus immune checkpoint inhibitor alone (7%, n = 1). Overall, heterogeneity of existing studies significantly limits generalizability of results. Further research is needed to reveal the potential role of OVs in the future of nonmelanoma skin cancer and cutaneous lymphoma treatment.